Engineering multi-agent systems : 7th International Workshop, EMAS 2019, Montreal, QC, Canada, May 13-14, 2019, revised selected papers /: 7th International Workshop, EMAS 2019, Montreal, QC, Canada, May 13-14, 2019, revised selected papers. (2020) - Unknown
No abstract available